Ecosystem of the University as a Subject of Educational Analytics - O. D. Shipunova; E. G. Pozdeeva; L. I. Evseeva (Дискурс, 2023)
Introduction. New trends in the philosophical analysis of higher education development are associated  with  the  prospects  for  an  interdisciplinary  approach  to  organizing  coordinated processes  in  the  multidisciplinary  university,  taking  into  account  the  peculiarities  of information and intellectual technology of digital culture. The University with the unity of its functional connections presents a complex multilevel ecosystem, which state is determined by the intersection of the interests of various subjects included into the vocational training system.  This  article  examines  the  convergence  processes  in  the  university  ecosystem associated  with  educational  strategy  planning,  in  particular  with  the  coordination  process between the university goals and expectations of employers and graduates.Methodology  and  sources. The  research  is  based  on  the  system  methodology  and principles of the communicative action theory. In the university ecosystem, the key role in the  functional  connections  organization  is  played  by  the  processes  of  convergence  in relation  to  the  intentions  of  the  participants  of  interaction  in  the  educational  space,  the identification of attitudes that motivate cooperation and mutual reinforcement of optimal behavioral strategies. The empirical basis is the statistical data from a number of sociological surveys  conducted  at  Peter  the  Great  St.  Petersburg  Polytechnic  University,  as  well  as research data on the target attitudes of companies in their interaction with universities.Results and discussion. Comparison of the level of consistency of companies' requests in finding employees and the educational goals of the university showed a common desire to form  a  high  potential  of  future  employees,  which  requires  pedagogical  technologies  to motivate  and  develop  project  skills  and  constructive  activities.  In  the  university development,  an  important  factor  is  the  formation  of  a  common  field  of  goals  and expectations realized in the graduate model, with account of the industry knowledge and new technologies development, as well as formation of skills that characterize the potential of self-development in the future profession.Conclusion. The  development  of  an  ecosystem  approach  in  the  analysis  of  modern university  activities  has  revealed  prospects  for  combining  university  knowledge  with practical  skills  in  planning  various  forms  of  partnership  with  business  and  other representatives  of  the  professional  community.  Convergence  processes  in  the  university ecosystem ensure the interpenetration of pedagogical technologies and agent strategies in achieving high-quality professional training.